Brief Review of the Results Regarding the Possible Underlying Mechanisms Driving the Neutrinoless Double Beta Decay - Neacsu, Andrei; Sevestrean, Vasile Alin; Stoica, Sabin (Frontiers in Physics, 2021)
Since the experimental discovery of neutrino oscillations, the search for the neutrinoless double beta decay has intensified greatly, as this particular decay mode, if experimentally discovered, could offer a testing ground for Beyond Standard Model (BSM) theories related to the yet hidden fundamental properties of neutrinos and the possibility of violating of some fundamental symmetries. In this work we make a brief review of the nuclear matrix elements and phase space factors calculations performed mainly by our group. Next, using these calculations and the most recent experimental half-life limits, we revise the constraints on the BSM parameters violating the lepton number corresponding to four mechanisms that could contribute to neutrinoless double beta decay. Finally, using the values obtained for the BSM parameters from one of the most sensitive double-beta decay experiments, we provide a comparison with the sensitivities of other experiments.